PENGELOLAAN DANA DAERAH DALAM PENANGGULANGAN STUNTING DI KABUPATEN PEMALANG TAHUN 2022 - Maharani, Putri Widiyana; Mutiarin, Dyah; Saputro, Muhammad Noor Cahyadi Eko (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Stunting is a nutritional problem that has not been properly addressed. The problem ofstunting cannot be remedied solely through incidental and partial measures. It must beaddressed comprehensively from its roots; hence, it is critical to do research focusedon finding a solution. The goal of this study is to determine the scope of the problemand how to combat stunting in Pemalang Regency. The research approach employedwas qualitative, with data collected through interviews, observation, and literaturereviews. The study comprised 10 villages with a high number of stunting cases:Jatingarang Village, Banjarmulya, Gondang, Kaligelang, the Islamic BoardingSchool, Kreyo, Banyumudal Village, Sima, Walangsanga, and Sugihwaras Village. Thestudy's findings indicated that the program for combating malnutrition in PemalangRegency had been properly resolved, with continual alignment of coaching and routineprograms, and was also supported by enough money from the Health OperationalAssistance, the Regional Government Budget, and the Revised Regional GovernmentBudget. The participation of the Health Office in the stunting prevention program waslisted in the